Absorption of Direct Oral Anticoagulants in Cancer Patients after Gastrectomy - Hannah C. Puhr; Aysegül Ilhan-Mutlu; Matthias Preusser; Peter Quehenberger; Paul A. Kyrle; Sabine Eichinger; Lisbeth Eischer (MDPI AG, 2022)
Direct oral anticoagulants (DOACs) are safe and effective in cancer patients treated for venous thromboembolism (VTE) or atrial fibrillation (AF). Gastrectomy is the treatment of choice in patients with localized upper gastrointestinal cancer. DOACs are absorbed in the upper gastrointestinal tract, but to what extent is unclear. In a retrospective analysis, hospital data were searched for adult patients who underwent gastrectomy for gastroesophageal or pancreatic cancer, and DOAC therapy for VTE or AF after gastrectomy. DOAC blood levels were determined by chromogenic assays before and after administration, and thromboembolic and bleeding complications were recorded. Eleven patients (median age 76 years) received a factor Xa inhibitor (FXaI; apixaban (3), edoxaban (3), rivaroxaban (4)) or the factor IIa inhibitor dabigatran (1) for VTE (7) or AF (4) after gastrectomy. Eight patients on FXaI had anti-Xa (aXa) trough levels within the expected range (ER). In all of them, aXa levels increased upon DOAC administration. Two patients on 30 mg edoxaban had low aXa trough levels. Administration of 20 mg of rivaroxaban resulted in trough levels in the ER in one of them. None of the FXaI patients had thromboembolism, while two experienced bleeding (arterial puncture site, gastrointestinal). One dabigatran AF patient with trough and peak concentrations below the ER had strokes during 110 mg and 150 mg dabigatran administration. While on apixaban, aXa levels were in the ER, and no clinical complications occurred. DOACs, particularly FXaI, were adequately absorbed in cancer patients after gastrectomy. Our observation of recurrent thromboembolic events in a patient treated with dabigatran warrants cautious use in this specific patient population.